Understanding the basics of electrotherapy, Glavnotherapy, Electrophoresis, Darsonvalization - Scientific advisor: Sattarov Yorqin Karimovich; Bekplatov Dilshod Bagrom ogli (Zien Journals, 2025)
The article discusses the methods of electrotherapy treatment with Glavnotherapy, Electrophoresis and Dorsonvalization in diseases such as neuralgia, vasculitis, diseases of the nervous system, rheumatism of the joints, neurasthenia.
Keywords: electric charges; frequency; Electrotherapy